2004
DOI: 10.1385/jmn:22:1-2:139
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Localization in the Neural Retina and Retinal Pigmented Epithelium of Embryonic Chicks

Abstract: It is well-established that growth hormone (GH) is present in the brain, spinal cord, and peripheral nerves of embryonic chicks, prior to the differentiation of pituitary somatotrophs, but its presence and distribution in retinal tissues is controversial. The possible presence of GH and GH mRNA in retinal tissues of early embryos has therefore been further evaluated. A 466-bp fragment of the pituitary GH cDNA, derived from a portion of exon 3 and spanning exons 4 and 5, was amplified by RT-PCR from reverse-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Our study is the first to present temporal and spatial regulation of the growth of an organelle. Recent studies have demonstrated that growth hormone (GH), the molecule in mammals mainly responsible for postnatal bone and muscle growth, is synthesized in chick retina and in retinal pigmented epithelial cells (RPE) from early stages of development (Harvey et al,2001,2004; Baudet et al,2003). GH receptor immunoreactivity was also detected in chick retina from E3 (Harvey et al,2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to present temporal and spatial regulation of the growth of an organelle. Recent studies have demonstrated that growth hormone (GH), the molecule in mammals mainly responsible for postnatal bone and muscle growth, is synthesized in chick retina and in retinal pigmented epithelial cells (RPE) from early stages of development (Harvey et al,2001,2004; Baudet et al,2003). GH receptor immunoreactivity was also detected in chick retina from E3 (Harvey et al,2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after secretion from the retina, this GH moiety is bound to a 45-kDa proteoglycan, opticin, in vitreous fluid [37]. GH immunoreactivity within the eye is also found in the choroid layer and in the retinal pigmented epithelium [38,39].…”
Section: Neural Retinamentioning
confidence: 99%
“…Studies in the developing chicken retina have localised GH to the cytoplasm of retinal ganglion cells and membranes of melanin granules [127]. IGF-I and GH have been reported to stimulate the proliferation of retinal progenitors in goldfish [121] and teleost [128,129] retina and IGF-I is neurogenic at the margin of the post-natal chicken retina [130].…”
Section: Gh and Igf-i And Neuro-genesis And Neuro-protectionmentioning
confidence: 99%